Ketamine alters behavior and decreases BDNF levels in the rat brain as a function of time after drug administration - Daiane B. Fraga; Gislaine Z. Réus; Helena M. Abelaira; Renata D. De Luca; Leila Canever; Bianca Pfaffenseller; Gabriela D. Colpo; Flávio Kapczinski; João Quevedo; Alexandra I. Zugno (Brazilian Journal of Psychiatry, 2013)
Objective: To evaluate behavioral changes and brain-derived neurotrophic factor (BDNF) levels in rats subjected to ketamine administration (25 mg/kg) for 7 days. Method: Behavioral evaluation was undertaken at 1 and 6 hours after the last injection. Results: We observed hyperlocomotion 1 hour after the last injection and a decrease in locomotion after 6 hours. Immobility time was decreased and climbing time was increased 6 hours after the last injection. BDNF levels were decreased in the prefrontal cortex and amygdala when rats were killed 6 hours after the last injection, compared to the saline group and to rats killed 1 hour after the last injection. BDNF levels in the striatum were decreased in rats killed 6 hours after the last ketamine injection, and BDNF levels in the hippocampus were decreased in the groups that were killed 1 and 6 hours after the last injection. Conclusion: These results suggest that the effects of ketamine on behavior and BDNF levels are related to the time at which they were evaluated after administration of the drug.